2009
DOI: 10.1152/ajpregu.90867.2008
|View full text |Cite
|
Sign up to set email alerts
|

Nesfatin-1 exerts cardiovascular actions in brain: possible interaction with the central melanocortin system

Abstract: Nesfatin-1 is a recently discovered hypothalamic peptide that was shown to suppress food intake through a melanocortin-3/4 receptor-dependent mechanism. Since nesfatin-1 mRNA is detected in the paraventricular nucleus of the hypothalamus, and because many peptides that alter food intake also influence cardiovascular function, we tested the ability of centrally administered nesfatin-1 to affect mean arterial pressure (MAP) in conscious, freely moving rats. Significant increases in MAP were observed following in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
192
1
5

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 177 publications
(211 citation statements)
references
References 27 publications
13
192
1
5
Order By: Relevance
“…Nucleobindin 2 is the precursor of a secreted calcium-binding protein, nesfatin-1, that influences the excitability of neurons in a part of the brain associated with stress and physiological changes (52). It stimulates autonomic nervous system activity, increases blood pressure (53), and has been associated with a range of brain functions, including the regulation of feeding. Nucleobindin induces fear and anxiety in rats (54).…”
Section: Resultsmentioning
confidence: 99%
“…Nucleobindin 2 is the precursor of a secreted calcium-binding protein, nesfatin-1, that influences the excitability of neurons in a part of the brain associated with stress and physiological changes (52). It stimulates autonomic nervous system activity, increases blood pressure (53), and has been associated with a range of brain functions, including the regulation of feeding. Nucleobindin induces fear and anxiety in rats (54).…”
Section: Resultsmentioning
confidence: 99%
“…This became more definite using higher dose of nesfatin-1. Yosten et al 4 did not find any change in heart rate after nesfatin-1 treatment during the light phase, but they measured it only for 1 h after injection.…”
Section: Discussionmentioning
confidence: 95%
“…There is a general consensus in the literature that nesfatin-1 itself is able to increase sympathetic activity, therefore such interaction is not surprising. 4,23 It is interesting, however, that there was no effect of nesfatin-1 on the heart rate applied at night, meanwhile a limited and belated (starting more than 1 h after injection) heart rate elevation was observed, when it was given during the light phase. This became more definite using higher dose of nesfatin-1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently studies have been shown an increasing blood pressure with administration of nesfatin-1. It has also been shown to play an important roles in the control of cardiovascular function (23,24). However, the effect mechanism of nesfatin-1 on the blood pressure is not clear.…”
Section: Introductionmentioning
confidence: 99%